System medicine approach to improve diagnosis and prognosis in Autism Spectrum Disorder (ASD), based on extensive genomic, biochemical and clinical data - Asif, Muhammad (2016)
Background: Autism Spectrum Disorder (ASD) is characterized by social communication impairments and repetitive behaviors, a clinical presentation spectrum and a high male to female ratio. Twin and family studies indicated a strong genetic basis for ASD, with approximately 20% of ASD etiologies residing with identified genetic abnormalities. Behavioral traits in the ASD spectrum are prevalent in unaffected family members, highlighting a trait heritability likely mediated by genetic factors that impact ASD risk. However, the impact of genetic factors on the phenotype and its variability is still not well understood. Due to the absence of underlying biological markers, ASD is still diagnosed by assessing the individual’s behavior. The understanding of the biological basis of ASD can contribute to an earlier diagnosis and then to early intervention, which can have a substantial positive effect on child developmen.